2014
DOI: 10.1155/2014/736298
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Cardiovascular Surgery in Elderly Patient: A Review of Current Options and Outcomes

Abstract: Due to the increase in average life expectancy and the higher incidence of cardiovascular disease with advancing age, more elderly patients present for cardiac surgery nowadays. Advances in pre- and postoperative care have led to the possibility that an increasing number of elderly patients can be operated on safely and with a satisfactory outcome. Currently, coronary artery bypass surgery, aortic and mitral valve surgery, and major surgery of the aorta are performed in elderly patients. The data available sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 111 publications
(119 reference statements)
1
57
0
5
Order By: Relevance
“…Regarding DM as other risk factor in our study, we found a significant correlation between DM and postoperative neurologic complications, this result was agreed with [16][17][18][19][20][21][22] they found a significant correlation between DM and postoperative neurologic complications and disagreed with [10][11][12][13] they found no significant correlation between DM and postoperative neurologic complications. Another risk factor which is dyslipidemia, in this study, there is a significant correlation between it and postoperative neurologic complications; this is agreed with [23][24][25][26][27][28][29] they found a strong and significant correlation between dyslipidemia and postoperative neurological complications. In this study, another risk factor is BMI; we find a significant correlation between BMI and postoperative neurologic complications and this result was agreed with [30][31][32] they found that BMI was a significant risk factor for prevalence of neurologic complications after CABG surgery, while this result disagreed with 33 who found that BMI has no impact on postoperative neurological complications.…”
Section: Discussion:-supporting
confidence: 89%
“…Regarding DM as other risk factor in our study, we found a significant correlation between DM and postoperative neurologic complications, this result was agreed with [16][17][18][19][20][21][22] they found a significant correlation between DM and postoperative neurologic complications and disagreed with [10][11][12][13] they found no significant correlation between DM and postoperative neurologic complications. Another risk factor which is dyslipidemia, in this study, there is a significant correlation between it and postoperative neurologic complications; this is agreed with [23][24][25][26][27][28][29] they found a strong and significant correlation between dyslipidemia and postoperative neurological complications. In this study, another risk factor is BMI; we find a significant correlation between BMI and postoperative neurologic complications and this result was agreed with [30][31][32] they found that BMI was a significant risk factor for prevalence of neurologic complications after CABG surgery, while this result disagreed with 33 who found that BMI has no impact on postoperative neurological complications.…”
Section: Discussion:-supporting
confidence: 89%
“…However, the study cohort was historical involving patients treated between 1984 and 1997. Given the overall prolonged life expectancy and the improved perioperative management in cardiac surgery (20), MVP should have led to more favorable outcomes currently. In the present study, we did not specially explore the potential factor accounting for the improved outcomes after MVP; however, they can be summarized from the other available evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulated evidence over the years shows that most cardiac surgical procedures can be performed in the elderly with very satisfactory outcomes. However, the risk in these patients for such procedures is only deemed acceptable in the absence of comorbidities (33). This holds true for TAVI procedures as well (34).…”
Section: Comorbiditiesmentioning
confidence: 99%